Characterization of patients that can continue conservative treatment for adenomyosis - Chiho Miyagawa; Kosuke Murakami; Takako Tobiume; Takafumi Nonogaki; Noriomi Matsumura (BMC, 2021)
Abstract Background Historically, hysterectomy has been the radical treatment for adenomyosis. Although, some patients may not want to have their uterus removed, patients often have to no choice but to request hysterectomy during conservative treatment. The factors necessitating these hysterectomies remain unknown. The purpose of this study was to determine which patients can continue conservative treatment for adenomyosis. Methods We selected women diagnosed with adenomyosis and provided with conservative treatment at the Kindai University Hospital and Osaka Red Cross Hospital in Osaka Japan from 2008 to 2017. Age at diagnosis, parity, uterine size, subtype of adenomyosis, type of conservative treatment, and timing of hysterectomy for cases with difficulty continuing conservative treatment were examined retrospectively. Results A total of 885 patients were diagnosed with adenomyosis, and 124 started conservative treatment. Conservative treatment was continued in 96 patients (77.4%) and hysterectomy was required in 28 patients (22.6%). The cumulative hysterectomy rate was 32.4%, and all women had hysterectomy within 63 months. In the classification tree, 82% (23/28) of women aged 46 years or younger were able to continue conservative treatment when parity was zero or one. In those with parity two and over, 95% (20/21) of those aged 39 years and older had hysterectomy. Conclusions Patients who continue conservative treatment for approximately 5 years are more likely to have successful preservation of the uterus. Multiparity and higher age at diagnosis are factors that contribute to hysterectomy after conservative treatment. Parity and age at diagnosis may be stratifying factors in future clinical trials of hormone therapy.